DETERMINATION OF HEAVY METALS ACCUMULATION IN TILAPIA FISH (Oreochromisniloticus) TISSUES HARVESTED FROM AJIWA DAM, BATAGARAWA, KATSINA STATE - Ahmad, Aliyu Abubakar; Abdulkarim, Isma’il; Usman, Hassan (FUDMA JOURNAL OF SCIENCES, 2023)
Aquatic animal species living in the wild like fishes came in contact with residences of heavy metals. Over time deposits of heavy metals are detected in tissues such as skin, muscles, gills, fin and bore. Concentration of heavy metals namely Au, Pb, Cd, Ag, As and Ca were detected in Tilapia Oreochromisniloticus tissues of Skin muscles, gills, fin and bone in this study. The fish samples were collected randomly from three fish landing sites at intervals of four weeks namely; Gajeren Giwa, Kwatami and Masabo sites A, B and C for analysis. Atomic Absorption Spectrophotometer (AAS) model A-6200, Agilent crop, Kyoto, Japan) was used for analysis. Results obtained revealed that the concentrations of heavy metals from Tilapia Oreochromisniloticus indicated Au, Pb, Cd, Ag, As and Ca levels (13.06ppm) to (7.73ppm) from skin and bone. 0.19) to 0.12 (ppm) (2519.87ppm) to (162.16ppm) (10.47ppm) to (0.31ppm), (0.75ppm), (0.75ppm), (0.28ppm) to (0.0ppm) from skin, muscles, gills, fin and bone (Ca>AU>Ag>As>PB>Cd). It showed significant difference in concentrations of metals with respect to the fish parts. Also the presence of reasonable concentrations Ag Cd, Pb, As and Ca reflects residues from fertilizer and herbicides application at farming sites proximity to the dam. The finding recommends Periodical studies of concentration of heavy metals should be mounted especially guided by seasonal variations unregulated use of fertilizers on farms neighboring the dam should be discouraged.
Keywords: Ajiwa Dam; Fish; Heavy metals Liquor; samples